Web-Based Information System of Financial Report (Case Study: CV. Jaya PPK Abadi Surakarta): Sistem Informasi Laporan Keuangan Berbasis Web (Studi Kasus CV. Jaya PPK Abadi Surakarta) - Pramanto, Andy; Naafian, Nuur Rochman; Wibowo, Kresno Ario Tri (Politeknik Harapan Bangsa Surakarta, 2023)
Financial statements are the most crucial information in controlling all financial activities of a company. Financial statements become very important because as a form of accountability and describing the conditions and controlling tools of the company. CV. Jaya PPK Abadi Surakarta is an agency engaged in advertising. The agency has problems in terms of preparing financial statements which are still carried out by collecting sales notes and purchase notes, then the total in one day is recorded on the financial statement book. This of course causes problems, including in terms of the past data search process and the risk of lost notes. The process of calculating financial statements is still carried out using a calculator and calculating the difference between all sales and purchases in one day, it causes problems when there is a miscalculation because it uses manual methods. The absence of preparing monthly financial statements also makes it difficult for leaders to see the details of sales, purchases and net profit of the company. This, of course, has a bad impact on the development of the company. The purpose of this study is to create a financial statement information system in CV. Jaya PPK Abadi Surakarta. The author uses the SDLC (System Development Life Cycle) method in the process of developing PHP systems and programming languages and using MySQL databases. The system that the author designed is expected to produce an application that can record incoming and outgoing financial data on the CV. Jaya PPK Abadi and can be accessed via the web so that leaders can immediately find out the entry and exit of financial flows.